Endoscopic submucosal dissection in large sessile lesions of the rectosigmoid: learning curve in a European center - Probst, A.; Golger, D.; Anthuber, M.; Märkl, B.; Messmann, H. (Endoscopy, 2012)
Background and study aims: Endoscopic submucosal dissection (ESD) in the colorectum is not currently a standard procedure. Few data are available from the Western world. The aim of the present study was to report on the first experiences and the learning curve of colorectal ESD in a European center.Patients and methods: A total of 82 rectosigmoid lesions were referred for ESD. Lesion characteristics, resection rates, procedure times, complications, and recurrences were recorded prospectively. Results were compared between three consecutive study periods in order to determine the learning curve.Results: Lesions were located in the rectum (86.6 %) and the sigmoid colon (13.4 %). Median diameter was 45.5 mm. Lesions were of Paris type 0-Is with pit pattern type V (n = 8), 0-IIa (n = 33), 0-IIa + Is (n = 36), and 0-IIa + IIc (n = 5). The malignancy rate in these groups was 100 %, 0 %, 14 %, and 20 %, respectively. ESD was possible in 76 lesions (92.7 %). En bloc resection rate and R0 resection rate were 81.6 % and 69.7 %, respectively. Median procedure time was 176 minutes. Between the three consecutive study periods, en bloc resection rate increased (60.0 %, 88.0 %, 96.2 %), R0 resection rate increased (48.0 %, 76.0 %, 84.5 %; P < 0.001), and procedure time decreased (200, 193, 136 minutes; P = 0.027). The perforation and bleeding rates were 1.3 % and 7.9 %, respectively. Recurrence risk was 0 % after R0 en bloc resection and 41.7 % after piecemeal resection (P < 0.05). Median follow-up was 23.6 months.Conclusions: In the European setting, ESD in the distal colon is feasible with acceptable complication risks. Resection rates were not as high as those from Japanese studies; however, a clear learning curve could be shown. Colorectal ESD needs to be further evaluated, particularly in Europe where ESD experience is low.